Review of the sustainable built environment in 1998–2015. Issue 2 (2nd April 2016) - Ubarte, Ieva; Kaplinski, Oleg
Abstract: A city is a complex physical and social phenomenon that is under constant development and undergoes quantitative and qualitative changes. The welfare of the whole society depends on the sustainability of the built environment. The article presents a review of the literature on the sustainable built environment, which was made on the basis of the Thomson Reuters Web of Science Core Collection database. The analysed articles were published between 1998 and 2015. The analysis of the number of publications was made according to years of publication, countries, research areas and the Web of Science categories. 31 article and review document type were selected for a detailed analysis by three key Web of Science categories: environmental science, environmental studies, and construction and building technology.